La frontera norte novohispana y la resistencia indígena, 1763-1785 (2016)
ABSTRACT: New Spain’s northern border could only be clearly delimited in the mid-eighteenth century as a consequence of the Bourbons’ military and administrative reforms in the area. Colonial rivalries demanded the maximization of all American income, and in the case of New Spain, new territories upstate became economically implicated whilst others were abandoned. Native resistance to the advance of the Spanish into these new territories was steadfast. This article offers an approach to the relationships between the Spanish Empire and the aboriginal tribes, as well as the appropriation and pacification policies employed between the Treaty of Paris in 1763 (which put an end to the Seven Years’ War) and the alliance formed between the Comanche and the Spanish against the Apache in 1785.